Power Quality Improvement by Upqc With Real Power Injected Micro Turbine - Ramesh, T.; Manimaran, S.; Kaliappan, S.; Emayavaramban, G.; Saravanan, R. (International Journal of Engineering and Technology, 2018)
Power Quality is one of the major concerns in the present system. Due to the rapid growth of non-linear loads, major power quality problems such as harmonics, unbalance operation and voltage deficiencies (i.e., sag and swell) arise. This paper proposes MTG based Unified Power Quality controller (UPQC) to get better the power quality troubles like voltage sag, current unbalance in the LV residential feeders which performs both the series and shunt operation. In this paper, Micro Turbine Generator (MTG) system is proposed to improve the efficiency and environmental benefits. The proposed system consists of two types, single shaft and split shaft MTG system. Among these two types, single shaft system is used which is simple in structure and easy to implement. The output of MTG system is connected to the DC link of UPQC. This proposed system reduces the THD content in the source voltage and load current of the system. The presentation of the projected system is imitation using the MATLAB / SIMULINK.Â